Pathology of severe urolithiasis in a flock of egg-laying hens - Lopes, Marcelo C.; Fonseca, Clarissa S.; Amaral, Camila I.; Saraiva, Luis H.; Oliveira, Letícia B.; Silva, Dayse H. L. da; Moreira, Matheus V. L.; Silva, Fabrício J. M. da; Armour, Natalie K.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2021)
Fourteen, 31-week-old Lohmann white layers from a flock of 30,000 chickens had a history of apathy, and a drop in egg production. Clinical signs were observed in approximately 40% of the flock, and lasted for three months. Fourteen hens were euthanized for post-mortem examinations. Macroscopic findings included marked atrophy and loss of renal lobes along with compensatory renal hypertrophy of the contralateral lobe. Ureters were markedly dilated and filled with mucus and/or with molded white to yellow-grey uroliths that obliterated the lumen. At histopathology, the uroliths inside ureters and tubules were composed of concentrically arranged mineralized concretions, as well as urates associated with heterophilic infiltrations and epithelial hyperplasia. Renal parenchyma adjacent to obstructed ureters was compressed with tubules replaced by fibrous tissue. Multifocal interstitial lymphocytic nephritis, proteinuria and membranoproliferative glomerulonephritis were also found. Heterophilic and caseous ureteritis associated with numerous Gram-positive coccoid bacteria occurred in three chickens. Immunohistochemistry for avian coronavirus was negative. This negative result along with the case history indicated that water restriction was the most likely cause of mortality. This condition resulted in significant economic loss for this farmer.